Teachers Education and the Didactics for Human Development - José Carlos Libaneo (Universidade Federal do Rio Grande do Sul, 2015)
The paper discusses the problem of decoupling and parallelism between two types of knowledge in the teacher education, the disciplinary knowledge and the pedagogical knowledge. Theoretical positions on this issue are presented, and next Davydov's teaching theory to human development is emphasized as an alternative to face the problem. Finally, it argues for its potential to understand the necessary link between didactics, specific didactics, and teaching methodologies to assure, in the curriculum, the interweaving of disciplinary knowledge and pedagogical knowledge.